If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4y + 2 + -1y + -9x + -5 = 0 Reorder the terms: 2 + -5 + 2x + -9x + 4y + -1y = 0 Combine like terms: 2 + -5 = -3 -3 + 2x + -9x + 4y + -1y = 0 Combine like terms: 2x + -9x = -7x -3 + -7x + 4y + -1y = 0 Combine like terms: 4y + -1y = 3y -3 + -7x + 3y = 0 Solving -3 + -7x + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + -7x + 3 + 3y = 0 + 3 Reorder the terms: -3 + 3 + -7x + 3y = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -7x + 3y = 0 + 3 -7x + 3y = 0 + 3 Combine like terms: 0 + 3 = 3 -7x + 3y = 3 Add '-3y' to each side of the equation. -7x + 3y + -3y = 3 + -3y Combine like terms: 3y + -3y = 0 -7x + 0 = 3 + -3y -7x = 3 + -3y Divide each side by '-7'. x = -0.4285714286 + 0.4285714286y Simplifying x = -0.4285714286 + 0.4285714286y
| 4.75t+5=13.5t+12 | | Y=cos(5*x)+sin(5*x) | | 3m-4n-7=8m+n-6 | | 24-8x=-2(4x+10) | | 3y+-5=5y | | 90+(3x-1)+31=180 | | 4.19/4 | | 7(5x-3)=10 | | 2x(100/45):3x(100/36) | | 9h-3-6h=16 | | 2(3x+6)+3(3x-4)= | | 0.06/1=x/30 | | 3z-4z=-30 | | 2+5=x-7 | | 4x-5(6x-6)=2-7(x-5) | | 1.14/1=x/30 | | 8-z=-22 | | 16/54 | | 4v-7v=-21 | | -20=7+9x | | 0.06/1=x/5 | | -7x+7=-5x+25 | | 0=4x^2+2x+32 | | K/-8.8=-12.9 | | (x)(-7)=42 | | 4(x-5)=7(2x-5) | | 2.40/1=x/60 | | -28=3(8a+4) | | 7x-5-x=15 | | -7x+12=8x-15 | | 4x+5y+4-y-6x-7= | | (-4)(x)=-20 |